POWER LOSS ANALYSIS OF A 1.5 MW THREE-PHASE SYNCHRONOUS GENERATOR UNIT 1 AT THE LOGAWA BASEH 1 MINI HYDROPOWER PLANT. - Fadhlan Hafizh Firmansyah; Adzin Murdiantoro, Randi; Wibowo, Rifqi; Fachruroji (Journal of Electronic and Electrical Power Applications, 2025)
This research was conducted during an Industrial Internship at PT Sumarah Energi with the objective of analyzing power losses in a 1.5 megawatt synchronous generator Unit 1 at the Logawa Baseh 1 Mini Hydropower Plant. The generator functioned to convert mechanical energy from the turbine into electrical energy; however, power losses occurred during operation, reducing the effective output power. The analysis was carried out by collecting generator specification data, stator current, excitation current, and daily load data during August 2025. The data were quantitatively analyzed through calculations of copper losses, core losses, mechanical losses, and stray load losses. The results showed that copper losses were the largest component of power losses, ranging from 15.12 to 21.25 kilowatts and increasing with higher stator current. Core losses of 9.19 kilowatts and mechanical losses of 6.12 kilowatts remained constant, while stray load losses contributed the smallest portion, ranging from 0.15 to 0.21 kilowatts. The total power losses ranged from 30.58 to 36.77 kilowatts and were mainly influenced by load variations caused by fluctuations in river water discharge. This research demonstrated that daily load variations significantly affected total power losses, particularly copper losses, while core and mechanical losses remained stable in synchronous generators used in mini hydropower plants.